Comparison of intra-articular lidocaine versus intravenous sedative and analgesic for reduction of anterior shoulder dislocation in terms of mean pain reduction using vas score - Akhtar, Rahman Rasool; Qammar, Muhammad Umair; Ahmed, Riaz; Arif, Adnan; Khan, Armaghana Qamar; Liaquat, Maria (Journal of Rawalpindi Medical College, 2023)
INTRODUCTION: The most common dislocation presenting to emergency department is anterior shoulder dislocation. Posterior dislocations and inferior dislocations are rare. Dislocations of the anterior shoulder mostly occur with the position of the arm is abducted and externally rotated. This results in injury of the humeral head, labrum, capsuloligamentous structures and glenoid. Such patients experience severe pain, therefore prompt reduction is necessary to ameliorate the pain. Intravenous analgesia combined with sedation or intra-articular lidocaine injection can be used for closed reduction of anterior shoulder dislocation. Due to its side effects, Intra-articular lidocaine (IAL) is recommended for use as a probable alternative to intravenous sedation-analgesia especially for patients with contraindication to intravenous sedation-analgesia. OBJECTIVE: To compare intra-articular lidocaine versus intravenous sedative and analgesic for management of anterior shoulder dislocation in terms of mean pain using VAS during reduction of shoulder joint. STUDT DESIGN: Randomized controlled trial (RCT). SETTING: Removed for blind review DURATION: 6 months (November 22nd, 2017 to May 21st, 2018) SAMPLE SIZE: 60 patients (30 in each group) RESULTS: We included sixty patients in my study. 19 (31.7%) were females and 41 (68.3%) were male patients. Out of all the patients 38 (63.3%) had right sided shoulder dislocation, while the rest 22 (36.7%) patients had left sided shoulder dislocation. Patients mean age was 33.27±10.535 years and mean pain score of all the patients was 4.966±1.930. The mean pain score in Group A was 4.200±1.648, while the mean pain score in Group B was 5.733±1.910 (p value = 0.002. Stratification was done according to gender and age group of the patients, and post-stratification t-test was applied. CONCLUSION: Intra-articular lidocaine is better option in pain control during reduction of anterior shoulder dislocation. KEY WORDS: Intra venous analgesia, Intra-articular lidocaine, shoulder dislocation.